Handbook of Energy Systems in Green Buildings (Springer Berlin Heidelberg, 2018)
This handbook provides a comprehensive summary on the energy systems used in green buildings, with a particular focus on solar energy - the most common renewable energy source applied in this field. With the growing concern about environmental protections, the concepts of green building have been widely promoted and implemented in nowadays building designs and constructions. Among all, sustainable energy systems, including energy harvesting, conversion, and storage, is one of most important design factors in green buildings. Unlike traditional energy systems which highly rely on fossil fuel, green buildings utilize renewable energy source or high efficient energy systems, or both, to provide environmental friendly, low carbon waste energy. The most updated concepts, designs, technologies developed and implemented in heat pumps, cooling systems, power systems, and energy storage will be discussed here in details. This handbook is subdivided into 7-9 main sections to provide an in-depth discussion from foundational principles to practical techniques. In addition, different cases about green energy systems implemented in global will be discussed. The book will be structured easy-to-read, to make it more accessible to graduate students and professionals in diverse scientific and engineering communities, including applied physics, civil engineering, electrical engineering, mechanical engineering, material engineering, and chemical engineering.